2009
DOI: 10.1152/ajpcell.00262.2009
|View full text |Cite
|
Sign up to set email alerts
|

Expression of plasmid DNA in the salivary gland epithelium: novel approaches to study dynamic cellular processes in live animals

Abstract: The ability to dynamically image cellular and subcellular structures in a live animal and to target genes to a specific cell population in a living tissue provides a unique tool to address many biological questions in the proper physiological context. Here, we describe a powerful approach that is based on the use of rat submandibular salivary glands, which offer the possibility to easily perform intravital imaging and deliver molecules from the oral cavity, and plasmid DNA, which offers the advantage of rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 45 publications
5
79
0
Order By: Relevance
“…Next, we analyzed the dynamics of F-actin recruitment onto the SCGs by transfecting the acini of live rats with GFP-lifeact, a probe that dynamically labels F-actin without compromising its function (37). We have previously shown that the acini in the SGs can be selectively transfected with fluorescently tagged proteins (27). As expected, in acinar cells, GFP-lifeact showed a distribution comparable to that of F-actin.…”
Section: F-actin Is Recruited On the Secretory Granules After Membranmentioning
confidence: 69%
See 3 more Smart Citations
“…Next, we analyzed the dynamics of F-actin recruitment onto the SCGs by transfecting the acini of live rats with GFP-lifeact, a probe that dynamically labels F-actin without compromising its function (37). We have previously shown that the acini in the SGs can be selectively transfected with fluorescently tagged proteins (27). As expected, in acinar cells, GFP-lifeact showed a distribution comparable to that of F-actin.…”
Section: F-actin Is Recruited On the Secretory Granules After Membranmentioning
confidence: 69%
“…Although we have successfully analyzed the dynamics of large SCGs (this study) and endosomal structure (27)(28)(29), it will probably be more difficult to study smaller structures such as 50-nm synaptic vesicles that exocytose in a few milliseconds. However, microscopes with faster scanning speed and genetically encoded probes with higher quantum efficiency may soon overcome this current difficulty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study has demonstrated that there is a difference in how transgenic hPTH is routed intracellularly between rat submandibular and parotid glands, and ultimately secreted. Using hPTH as a model protein to study the sorting pathways operative in these two exocrine glands should lead to a better understanding of how transgenic proteins are handled in salivary epithelial cells and, presumably, result in the identification of the key intracellular molecules involved (Baum, 2009;Sramkova et al, 2009). The latter, along with large animal studies, likely would permit a reasonable assessment of the potential to find similar endocrine sorting of transgenic hPTH in human parotid glands as seen herein with the rat parotid gland.…”
mentioning
confidence: 99%